Analisa Hukum Penerapan Restorative Justice dalam Tindak Pidana Kecelakaan Lalu Lintas di Tahap Penyidikan - Rahmat Zarkasih Londa; Hartoyo Hartoyo; Nasoetion, Dedi Wardana; Sri Astutik (International Forum of Researchers and Lecturers, 2025)
This study examines the application of restorative justice in traffic accidents during the investigation stage. The main focus of this research is to analyze the regulations and implementation process. The goal is to comprehensively describe how restorative justice policies are regulated by law and how they are practiced in the field, particularly by investigators. The research method used is a juridical- normative method with a qualitative approach. Data were obtained through literature review and in-depth interviews with relevant parties. The results indicate that restorative justice can be applied in resolving traffic accident cases, especially those resulting in minor losses or minor injuries. This regulation is contained in various regulations, such as Police Regulations and Circular Letters that serve as guidelines for investigators. The implementation process involves mediation between the perpetrator, the victim, and other relevant parties to reach a peaceful agreement. This agreement often includes compensation, an apology, or other mutually agreed-upon forms of reparation. The application of restorative justice aims to restore conditions to normal, restore social relationships, and avoid lengthy formal judicial processes. However, its implementation still faces challenges, such as unequal public legal awareness and the criteria for cases that can be resolved through restorative justice.